Comparative Evaluation of Razumab and Accentrix in Diabetic Macular Edema: Effects on Visual Acuity and Central Macular Thickness - Varshney, Shubhi; Sengupta, Roshni (Journal of Neonatal Surgery, 2025)
Background: Diabetic retinopathy is a microvascular disorder occurring as a long-term effect of diabetes mellitus. It may lead to vision-threatening damage to the retina that will eventually lead to blindness. It is the most common cause of severe vision loss in adults of working age groups in India and the Western world. Early detection and timely intervention are crucial in preventing blindness caused by diabetic retinopathy. Currently, anti-VEGF agents are the first-line treatment for central macular edema. Ranibizumab has beneficial effects in patients with baseline good visual acuity. This study aimed to find out the differences between the effects of Biosimilar and cost-effective Razumab and the Innovator brand Accentrix in terms of improving Visual Acuity and reducing Central Macular Thickness. Materials and Methods: This randomised comparative study was done at Krishna Netralaya from March 2024 to December 2024. A total of 38 eyes were taken having Diabetes and were diagnosed with Diabetic Macular Edema. They were randomly given anti-VEGF injections, Razumab and Accentrix. They were divided into Group R (Razumab)= 14 and Group A (Accentrix)= 24. Result: Improvement was comparable between two groups, Group A and group R in terms of Visual Acuity (p<0.05) whereas CMT showed statistically significant differences with Accentrix injection (p<0.05), but showed no statistically significant differences with Razumab injection (p>0.05) with Wilcoxon W test. Conclusion: Anti VEGF injection is a safe and effective treatment in case of Diabetic Macular Edema irrespective of age at the time of treatment. While both agents are effective in improving visual outcomes, Accentrix offer superior anatomical benefits. Further studies with larger sample sizes and longer follow-up are warranted to confirm these results and guide clinical decision-making